The Role of Organizational Commitment and Information System towards the Employees Performance - Arief Maulana; Herman Soegoto (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research is conducted to find out the role of organizational commitment and information system in improving the employees performance in Sekretariat Dewan Perwakilan Rakyat Daerah (DPRD) Kabupaten Bandung Barat. Descriptive analysis method is used by collecting various data from human resource department as well as conducting interview with the employees of Sekretariat Dewan Perwakilan Rakyat Daerah. The result shows that the implementatiom of information system results in the improvement of employees performance. Moreover, the organizational commitment has also met the organizational needs. Therefore, the implementation of informatiom system and organizational commitment affect the improvement of employees performance of Sekretariat DPRD Kabupaten Bandung Barat